Respons Instansi Terhadap Program Kiwari Rri Bogor Dalam Pelayanan Publik (Rumah Sakit PMI dan PT TASPEN Bogor) - C Maydiana; Amiruddin Saleh (Institut Pertanian Bogor, 2011)
ABSTRACT The RRI Bogor Kiwari’s program besides has a role to increase the quality of public service which helped by dependent instances like The Indonesian Red Cross Hospital and PT TASPEN in Bogor also has other role to provide public service to fulfill the listener’s needs that effected the listener’s satisfaction to the instances worthiness services through Bogor Kiwari’s programme as a place to keep and tell the society’s sights. The aims of this research are: (1) to analyze the instances’s responses to the Kiwari RRI Bogor’s programme of public services in Bogor, (2) to analyze the actions of professional instances services in Bogor, (3) to analyze the models of professional instances services to public in Bogor. The data were taken and collected on January until February 2010. This research was used constructivist paradigm. The research subjects and key informans were the leaders and staffs of The Indonesian Red Cross Hospital and PT TASPEN in Bogor that became a messenger as speakers in Bogor Kiwari’s talk show programme and also RRI Bogor’s staff who concerned about Bogor Kiwari’s programme. The data were taken by using technique of data collection through: document study, observation, indepth interview and FGD. The results of this research were: (1) Bogor Kiwari’s programme got enough satisfaction responses from The Indonesian Red Cross Hospital and PT TASPEN in Bogor; (2) The Indonesian Red Cross Hospital and PT TASPEN in Bogor when done the actions had three aspects, namely: (a) quality of service, (b) efficiency and appropriate actions, (c) employee rationalization; (3) The services strategies that done by The Indonesian Red Cross Hospital and PT TASPEN in Bogor were quick and exact service to overcome public’s sights, had coordination with government, given the satisfy facilitations. Key words: responses, Kiwari RRI Bogor’s programme, the instances’s actions, public services